In Vitro Determine the Cytotoxicity of Cerium Oxide Nanoparticles Against HBL-100 and ‎Rat’s Embryonic Fibroblast (REF) Cell Lines - Sundus Jaffar Razak, Ali A.A. Al-Ali (Basrah Journal of Veterinary Research)
This work was conceived as a contribution to the study of the cytotoxicity of different ‌concentrations of cerium ‌oxide nanoparticles (CeO2NPs≥25nm, nanoceria) (10, 30, 60, 90, and 120 ‌‌µg/ml) against two cell lines involves breast epithelial HBL-100 and Rat’s Embryonic Fibroblast ‌‌(REF) in vitro, by using MTT assay technique. The results showed that the nanoceria reduced ‌significantly the cell viability of HBL-100 at all concentrations compared with the control, except ‌the concentration 60 µg/ml that reduced the cell viability without significant differences compared ‌with control, the IC50 value of the nanoceria for the HBL-100 was 81.00 µg/mL. While, the cell ‌viability of REF was reduced with high significant difference by all nanoceria’s concentrations ‌compared with control, and the IC50 value of the nanoceria was 1.56 µg/mL. So, we ‌may conclude ‌that nanoceria with the >25nm particle size have high cytotoxicity for REF cell line at low and ‌high concentration compared with the HBL-100 cell viability that decreased exponentially with ‌the concentration. ‌